Integrating Social and Behavioral Sciences Into the Pakistani Medical Curriculum is Essential - Tayyeba Iftikhar Mirza, Shazia Inam, Saira Rahim, Momina Haq, Aisha Liaquat, Mufassar Nishat, (Pakistan Journal of Medical & Health Sciences, 2023)
The majority of respondents who took part in a survey were of the opinion that there should be a greater focus placed on behavioural and social sciences within the curriculum of medical schools. This is done to ensure that graduates of medical schools will be able to practise medicine in a manner that is both safe and effective. Despite the fact that behavioural and social sciences make significant contributions to the effectiveness of health care delivery, traditional medical school curricula have not traditionally placed a significant amount of focus on the study of these subjects. This article's objective is to provide the reader with a more in-depth comprehension of the value of social and behavioural sciences in medical education as well as the breadth of their application in a variety of different settings. Additionally, it discusses the areas of social and behavioural sciences that are significant to medicine, as well as the efficacy of incorporating them into the curricula of medical schools in order to educate and train future medical professionals to practise medicine in a manner that is fully informed. Place of Study: Foundation University Islamabad Study Duration: February 2022 to July 2022 Study Design: Empirical research Conclusion: This study examines the importance of teaching future doctors about medicine's social and behavioural aspects. It gives medical school educators the latest information on how to best teach medical students to succeed in the medical industry. Medical educators, administrators, policymakers, and other stakeholders must work together to integrate social and behavioural sciences into medical curricula. Keywords: Medical curriculum's courses, the social and behavioral sciences, and the foundations of medical education.